Efisiensi Belanja Daerah Dan Cointegrasi Kemiskinan di Provinsi Aceh - Irfan Irfan; Nabilatul Jannah; Isthafan Najmi; Yuni Ayu Safitri (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
The purpose of this study was to determine the efficiency level of the Special Autonomy profit sharing fund, tax sharing and social assistance spending and its effect on poverty rates in 23 districts/cities in Aceh Province. The sample for this study uses combined data from regions (districts/cities) and the time period from 2015-2020. Methods This study uses two analytical approaches, namely Data Envelopment Analysis (DEA) to measure output efficiency with return to scale variables and Panel Regression using the Random Effects approach to see its effect on poverty. From the results of the research, there were only six districts that were efficient in terms of aid spending. social assistance or 26 percent while the remaining 74 percent of urban districts are not yet efficient in terms of using public spending on social assistance in the province of Aceh, then the results of the random effect panel regression of the social assistance program (PKH) and the human development index (IPM) have a negative and significant effect on the level of poverty in Aceh province